Stream Discharge Analysis Under Different Forest Covers: a Case Study from Paired Microwatersheds of Garhwal Himalaya, India - Tiwari, Rajeev Kr.; Rai, S. P.; Qazi, N.; Kumar, Bhishm (Indian Forester, 2011)
Two microwatersheds namely Arnigad and Bansigad near Mussoorie, equipped with hydrometeorological instruments were selected to monitor the impact of forest cover on stream discharge. Arnigad microwatershed is having dense forest cover and Bansigad is with degraded forest. Total rainfall received in the Arnigad and Bansigad micro watersheds are 2905 mm and 2958 mm, generating runoff of 1627 mm and 1932 mm respectively during the year 2008-09. During the monsoon period from June to September, 2008 both the watersheds r eceived about 86-88% of the total rainfall while runoff per centage during June to September was 81% in Bansigad and 60% in Arnigad watershed. Total annual discharge of the stream under degraded forest cover was higher by 305 mm (19%). Total stream discharge under dense forest during the non monsoon period from October, 2008 to March, 2009 was higher by 50%.